Protecting Children from Cybercrime : Legislative Responses in Latin America to Fight Child Pornography, Online Grooming, and Cyberbullying through Information and Communication Technologies - Dos Santos Lemos Fernandes, Simone (World Bank, Washington, DC, 2016)
This regional study is focused on the prevention and combat of violence against children through the internet in Latin American countries in order to illuminate problems shared by the different countries, identify the gaps in legislation, and highlight good practices in the prevention and protection of minor victims of online sexual exploitation. Framed by international and regional standards on the protection of children from online exploitation, this regional study consists of an analysis of national legislation, regulation, and private and public policy responses to protect children from violence and sexual abuse through the use of the internet and new media and technologies. The analysis reviewed constitutions and domestic laws assessing their compliance with international instruments and verifying the progress made in harmonizing with international patterns. This regional study is focused on child abuse images (CAI), more commonly identified as child pornography, and online grooming, cyberbullying, and sexting, which are the most common offenses perpetrated online that threaten a child’s right to a healthy life and sexual dignity. It takes into account research and studies related to the use and misuse of information and communication technologies (ICTs), official statistics related to crimes committed against children through the internet, and the use of ICTs by children, specifically reports produced by the International Telecommunication Union (ITU), Council of Europe (CoE), United Nations Childrens Fund (UNICEF), End Child Prostitution, Child Pornography and Trafficking of Children for Sexual Purposes (ECPAT), and the International Centre for Missing and Exploited Children (ICMEC). Doctrine and interviews with national authorities dealing directly with these issues were also considered.